Extending Raspberry Shelf Life and Maintaining Postharvest Quality with CO2 Atmospheres - Mohd Rezaul Islam; Elizabeth Mitcham (Horticulturae)
Raspberry (Rubus idaeus L.) fruit are known for their extremely short shelf life. Decay, leakiness, and loss of firmness are the most common limiting factors contributing to their short storage life. However, storage in elevated CO2 and reduced O2 atmospheres can delay senescence in fruit by reducing softening, respiration and ethylene production rates, and pathogen growth. In this study, raspberries were exposed to four different CO2 atmospheres—15 kPa CO2 and 6 kPa O2 (15 kPa); 8 kPa CO2 and 13 kPa O2 (8 kPa); 5 kPa CO2 and 16 kPa O2 (5 kPa); or 0.03 kPa CO2 and 21 kPa O2 (0.03 kPa)—and were evaluated for their postharvest quality periodically during two weeks of storage in 2020 and 2021. Raspberry fruits kept in a 15 kPa CO2 atmosphere followed by 8 kPa CO2 had higher firmness, brighter red color, and the least fungal decay or leakiness. In all atmospheres, the total anthocyanin content increased over time, although the rate of increase was slowed by high CO2. The raspberries’ visual attributes deteriorated over time in all atmospheres, but high CO2 atmospheres slowed the rate of deterioration. After five days, the quality of air-stored raspberries was significantly degraded, while the raspberries stored in elevated CO2 maintained good quality for up to ten days.